Birger Kaipiainen - Kalha, Harri, 1962-; Laakso-Tammisto, Liisa; Siltavuori, Emilia; Valtiala, Robin (Helsinki : Suomalaisen Kirjallisuuden Seura, 2013)
Birger Kaipiainen i ett nötskal.
Birger Kaipiainen in a nutshell.
Sisältää bibliografisia viitteitä.
Keywords: henkilöhistoria; keramiikkataide; keramiikkataiteilijat; muotoilijat; taideteollisuus; teollinen muotoilu; personhistoria; keramikkonst; keramiker; formgivare; konstindustri; industriell formgivning; Suomi; Finland; Kaipiainen, Birger; näyttelyjulkaisut; utställningskataloger